Adjuvant statin therapy for oesophageal adenocarcinoma: the STAT‐ROC feasibility study. Issue 1 (14th December 2019) - Alexandre, L.; Clark, A. B.; Walton, S.; Lewis, M. P.; Kumar, B.; Cheong, E. C.; Warren, H.; Kadirkamanathan, S. S.; Parsons, S. L.; Dresner, S. M.; Sims, E.; Jones, M.; et al.
Abstract : Background: Statins inhibit proliferative signalling in oesophageal adenocarcinoma (OAC) and their use is associated with better survival in observational studies. The present study was undertaken to examine the feasibility of assessing adjuvant statin therapy in patients with operable OAC in a phase III RCT. Methods: For this multicentre, double‐blind, parallel‐group, randomized, placebo‐controlled feasibility trial, adults with OAC (including Siewert I–II lesions) who had undergone oesophagectomy were centrally allocated (1 : 1) to simvastatin 40 mg or matching placebo by block randomization, stratified by centre. Participants, clinicians and investigators were blinded to treatment allocation. Patients received treatment for up to 1 year. Feasibility outcomes were recruitment, retention, drug absorption, adherence, safety, quality of life, generalizability and survival. Results: A total of 120 patients were assessed for eligibility at four centres, of whom 32 (26·7 per cent) were randomized, 16 in each group. Seven patients withdrew. Participants allocated to simvastatin had lower low‐density lipoprotein cholesterol levels by 3 months (adjusted mean difference −0·83 (95 per cent c.i. −1·4 to −0·22) mmol/l; P  = 0·009). Median adherence to medication was greater than 90 per cent between 3 and 12 months' follow‐up. Adverse events were similar between the groups. Quality‐of‐life data were complete for 98·3 per cent of questionnaire items. Cardiovascular disease, diabetes and aspirin use were more prevalent in the non‐randomized group, whereas tumour site, stage and grade were similar between groups. Survival estimates were imprecise. Conclusion: This RCT supports the conduct and informs the design considerations for a future phase III trial of adjuvant statin therapy in patients with OAC. Registration number: ISRCTN98060456 (www.isrctn/com ). Abstract : After oesophagectomy for oesophageal adenocarcinoma (OAC), the 5‐year survival rate is currently only 30 per cent. There is strong observational evidence that statin use is associated with reduced all‐cause and cancer‐specific mortality in patients with OAC. This multicentre, double‐blind, parallel‐group, randomized, placebo‐controlled trial has established the feasibility of a future phase III trial of adjuvant statin therapy in patients treated with curative intent for invasive OAC. Justification for a full trial Abstract : Antecedentes: Las estatinas inhiben las señalizaciones proliferativas en el adenocarcinoma de esófago ( oesophageal adenocarcinoma, OAC) y su uso se asocia con mejor supervivencia en estudios observacionales. El presente estudio se llevó a cabo para examinar la viabilidad de evaluar el tratamiento adyuvante con estatinas en pacientes con OAC operable en un ensayo aleatorizado y controlado de fase III. Métodos: En este ensayo de viabilidad controlado por placebo, aleatorizado, de grupos paralelos, doble ciego y multicéntrico, los pacientes adultos con OAC (incluyendo lesiones Siewert I/II) que fueron sometidos a esofaguectomía se asignaron de forma centralizada (1:1) a tratamiento con simvastatina 40 mg o placebo equivalente mediante aleatorización en bloques, estratificados por centro. Los participantes, los clínicos y los investigadores desconocían la asignación del tratamiento. Los pacientes recibieron el tratamiento hasta un año. Los resultados de viabilidad fueron reclutamiento, retención, absorción del fármaco, adherencia, seguridad, calidad de vida, generalización, y supervivencia. Resultados: Un total de 120 pacientes fueron evaluados para elegibilidad en 4 centros, de los cuales 32 (26, 7%) fueron aleatorizados, 16 en cada grupo. Siete pacientes abandonaron el ensayo. Los pacientes asignados a tratamiento con simvastatina tenían niveles de colesterol LDL más bajos a los 3 meses (diferencia media ajustada, −0, 83 mmol/L, i.c. del 95% −1, 4 a −0, 22, P = 0, 009). La mediana de la adherencia a la medicación fue mayor del 90% entre los 3‐12 meses de seguimiento. Los eventos adversos fueron similares entre los grupos. Los datos de calidad de vida estaban completos en el 98, 3% de las preguntas del cuestionario. Enfermedad cardiovascular, diabetes y uso de aspirina eran más prevalentes en el grupo no aleatorizado, mientras que la localización del tumor, el estadio y el grado fueron similares entre los grupos. Las estimaciones de supervivencia fueron imprecisas. Conclusión: Este RCT apoya la realización e informa de las consideraciones de diseño para un futuro ensayo de fase III de tratamiento adyuvante con estatinas en pacientes con OAC.